2010
DOI: 10.1103/physrevd.82.044036
|View full text |Cite
|
Sign up to set email alerts
|

Holographic non-Fermi liquid in a background magnetic field

Abstract: We study the effects of a non-zero magnetic field on a class of 2+1 dimensional nonFermi liquids, recently found in [1] by considering properties of a Fermionic probe in an extremal AdS 4 black hole background. Introducing a similar fermionic probe in a dyonic AdS 4 black hole geometry, we find that the effect of a magnetic field could be incorporated in a rescaling of the probe fermion's charge. From this simple fact, we observe interesting effects like gradual disappearance of the Fermi surface and quasi par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 19 publications
1
45
0
Order By: Relevance
“…When a finite U (1) charged density in the fermionic sector is introduced in the holographic system, it is natural to ask whether the system possesses a Fermi surface and what is the low energy excitations. There have been some progresses in studying the fermionic sector, where a number of generic couplings for the fermions have been realized [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Recently, introducing the coupling between the fermion and gauge field through a dipole interaction in the bulk, it was remarkably found that as the strength of the interaction is varied, spectral density is transferred and beyond a critical interaction strength a gap opens up [25].…”
Section: Introductionmentioning
confidence: 99%
“…When a finite U (1) charged density in the fermionic sector is introduced in the holographic system, it is natural to ask whether the system possesses a Fermi surface and what is the low energy excitations. There have been some progresses in studying the fermionic sector, where a number of generic couplings for the fermions have been realized [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Recently, introducing the coupling between the fermion and gauge field through a dipole interaction in the bulk, it was remarkably found that as the strength of the interaction is varied, spectral density is transferred and beyond a critical interaction strength a gap opens up [25].…”
Section: Introductionmentioning
confidence: 99%
“…For the RN-AdS 4 background, fermion correlators in the dual boundary theory have been studied extensively; see, for example, [24,41,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. A similar kind of analysis can be done here for the electron star background.…”
Section: Discussionmentioning
confidence: 87%
“…Investigation [53] is also of interest, as an approach to the Green's functions calculation in the presence of magnetic field was evolved in this work and prospects of this approach application in the Hall quantum effect physics were discussed.…”
Section: Further Development Of the Approachmentioning
confidence: 99%